PEMBERDAYAAN ORGANISASI KARANG TARUNA DI DESA TEWASEN KECAMATAN AMURANG BARAT KABUPATEN MINAHASA SELATAN - LANGKAY, EBEN RIAN; DENGO, SALMIN; KOLONDAM, HELLY (JURNAL ADMINISTRASI PUBLIK, 2022)
In society, there are many youth organizations including youth organizations, but youthorganizations are different from other youth organizations both in terms of position and function. KarangTaruna is an organization formed by the community as a potential and source of social welfare with thetask of developing the potential of the younger generation and society as well as playing an active role inpreventing and overcoming social problems. The purpose of this research is to find out how to empoweryouth organizations in Tewasen Village, West Amurang District, South Minahasa Regency. The researchmethod used is a qualitative method. Informants in research are people who can provide informationabout research. The focus of the research is seen from the indicators according to Rairan, namely therole/facilitative efforts and educational roles/efforts. Data collection techniques through interviews,documentation and observation. The results showed that the empowerment of youth organizations throughfacilitative roles/efforts and the empowerment of youth organizations through educational roles/effortshad not been maximized in other words all roles/efforts had been implemented but not yet maximized.Keywords : Empowerment, Organization, Youth Organization